In vitro Activity of Cefiderocol Against Gram-Negative Clinical Isolates Collected from Urinary Track Source: SIDERO-WT-2014/SIDERO-WT-2015. (4th October 2017) - Tsuji, Masakatsu; Hackel, Meredith; Echols, Roger; Yamano, Yoshinori; Sahm, Dan
Abstract: Background: The global rise of carbapenem resistant Gram-negative bacteria such as carbapenem-resistant Enterobacteriaceae (CRE) and carbapenem-resistant non-fermenting bacteria is alarming and become threats to patient as only a few drugs remain active (e.g. colistin). Cefiderocol (S-649266) is a novel parenteral siderophore cephalosporin with potent activity against a wide variety of Gram-negative pathogens including carbapenem-resistant strains. This study evaluated the in vitro activity of cefiderocol and comparator agents against clinical isolates collected from urinary track source from North America. Methods: A total of 3, 323 Enterobacteriaceae, 263 Acinetobacter spp, 509 Pseudomonas aeruginosa, and 38 Stenotrophomonas maltophilia collected from the USA and Canada in 2014–2016 were tested. MIC was determined for cefiderocol, cefepime (FEP), ceftazidime-avibactam (CZA), ceftolozane-tazobactam (C/T), ciprofloxacin (CIP), colistin (CST), and meropenem (MEM) by broth microdilution and interpreted according to CLSI 2016 guidelines. All testing was done at IHMA, Inc. As recommended by CLSI, cefiderocol was tested in iron-depleted cation-adjusted Mueller Hinton broth. Based upon CLSI breakpoints, carbapenem-non-susceptible (CarbNS) strains were defined as follows: MEM: MIC ≥2 µg/mL for Enterobacteriaceae, ≥4 µg/mL for non-fermenters. Quality control testing was performed on each day of testing by using E. coli ATCC25922 and P. aeruginosa ATCC27853. Results: Cefiderocol exhibited in vitro activity against 4, 133 strains of Gram-negative bacteria with an overall MIC90 of 0.5 µg/mL. At 4 µg/mL cefiderocol inhibited the growth of 99.9% of the all isolates. MIC90 of cefiderocol against CarbNS Enterobacteriaceae was 4 µg/mL although MIC90 of other comparators were >64 or >8 (CST) µg/mL. The cefiderocol MIC90 value was 1 µg/mL for CarbNS non-fermeneters. Conclusion: Cefiderocol demonstrated potent in vitro activity against Enterobacteriaceae, A. baumannii, P. aeruginosa, and S. maltophilia isolates collected from a UTI source, with greater than 99.9% of isolates having MIC values ≤4 µg/mL. These findings indicate that this agent has high potential for treating cUTI infections caused by these problematic organisms, including isolates resistant to colistin. Disclosures: M. Tsuji, Shionogi & Co.: Employee, Salary; M. Hackel, IHMA: Employee, Salary; R. Echols, Shionogi & CO., LTD: Consultant, Consulting fee; Y. Yamano, Shionogi & Co.: Employee, Salary